The Influence of Leader-Member Exchange and Affective Commitment on Organizational Citizenship Behavior - Dede Suhendi; Windi Matsuko Danasasmita (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This study uniquely focuses on the impact of Leader-Member Exchange (LMX) and affective commitment on Organizational Citizenship Behavior (OCB) at the Yamaha Flagship Shop, a prominent company in the automotive sector, located in the vibrant city of Bandung. OCB, which refers to the voluntary actions of employees that contribute to the business's effectiveness, is a key area of investigation. The research methodology is a quantitative technique combining descriptive and verification methods. The study collected samples from 35 respondents who were employees of the Yamaha Flagship Shop in the Bandung City branch. The data and information utilized in this study consist of primary data acquired directly from companies, as well as secondary data sourced from books, journals, and the Central Bureau of Statistics (BPS). The findings of this study are significant as they indicate a robust correlation of 0.832 between the Leader-Member Exchange variable and the Affective Commitment variable at the Bandung City branch of the Yamaha Flagship Shop. This correlation is statistically significant with a p-value of 0.000. The Leader-Member Exchange variable has a positive and statistically significant effect of 0.410 on Organizational Citizenship Behavior. The Affective Commitment variable shows a positive and statistically significant effect of 0.569 on Organizational Citizenship Behavior. The direct impact of Leader-Member Exchange and Affective Commitment on Organizational Citizenship Behavior is 16.8% and 32.4%, respectively. Each of the indirect effects accounted for 19.4% of the total, resulting in a cumulative total of 88%. These findings underscore the substantial impact of Leader-Member Exchange and Affective Commitment on the Organizational Citizenship Behavior of the Yamaha Flagship Shop in the Bandung City Branch, providing valuable insights into organizational behavior.